Seasonal changes of δD and δ18O in tree-ring cellulose of Quercus crispula suggest a change in post-photosynthetic processes during earlywood growth. (15th June 2018) - Nabeshima, Eri; Nakatsuka, Takeshi; Kagawa, Akira; Hiura, Tsutom; Funada, Ryo
Abstract: Leaf photosynthetic and post-photosynthetic processes modulate the isotope ratios of tree-ring cellulose. Post-photosynthetic processes, such as the remobilization of stored starch in early spring, are important to understanding the mechanisms of xylem formation in tree stems; however, untangling the isotope ratio signals of photosynthetic and post-photosynthetic processes imprinted on tree rings is difficult. Portions of carbon-bound hydrogen and oxygen atoms are exchanged with medium water during post-photosynthetic processes. We investigated the δD and δ 18 O values of tree-ring cellulose using Quercus crispula Blume trees in two different habitats to evaluate seasonal changes in the exchange rate ( f -value) of hydrogen or oxygen with medium water, and examined the associations of the post-photosynthetic processes. Theoretically, if the f -value is constant, δD and δ 18 O would be positively correlated due to meteorological factors, while variation in the f -value will create a discrepancy and weak correlation between δD and δ 18 O due to the exchange of carbon-bound hydrogen and oxygen with medium water. The values of δD decreased drastically from earlywood to latewood, while those of δ 18 O increased to a peak and then decreased toward the latewood. The estimated seasonal f -value was high at the beginning of earlywood and decreased toward the latewood. The post-photosynthetic processes associated with changes in the f -value were the remobilization of stored starch and triose cycling during cellulose synthesis because of the shortage of photo-assimilates in early spring. Although we did not evaluate relevant physiological parameters, the seasonal pattern of δD and δ 18 O in tree-ring cellulose of Q. crispula was clear, suggesting that the dual isotope (δD and δ 18 O) approach can be used to reveal the resource allocation mechanisms underlying seasonal xylem formation.